An acoustic study of shorea leprosula wood fiber filled polyurethane composite foam - Mohd Azahari, Muhammad Shafiq; M. Rus, Anika Zafiah; Kormin, Shaharuddin; Zaliran, M. Taufiq (The Malaysian Analytical Sciences Society, 2018)
Polyurethane foam is an excellent material for sound absorbing materials. This material is produced by mixing crosslinker, and polyol to produce foams with the presence of blowing agent. This study consists of an experimental study on acoustics properties enhancement of polyurethane foam by mixing different weight percentage of Shorea leprosula wood fiber into the polymer matrix. An optimal percent of 5-20% wood fiber was used to obtain a homogeneous mixture. The polymer foam composites acoustic properties were measured by using impedance tube test to obtain the sound absorption coefficient. The polymer foam composites UF80 produced have a better sound absorption coefficient, α of 0.9507. UF80 gives a higher density of 865.5 kg/m3 and smallest pore size of 413.4 μm which is determined by using Mettler Toledo Density kit and Scanning Electron Microscope (SEM) respectively compared to UF. The noise reduction coefficient (NRC) of the polymer foam composites UF80 is twice as high as UF. This studies proved that Shorea Leprosula wood fiber influenced the acoustic properties of polymer foam composites.